Kinerja: a workflow execution environment - Procter, Sam (Kansas State University, 2011)
Like all businesses, clinical care groups and facilities are under a range of pressures to enhance the efficacy of their operations. Though there are a number of ways to go about these improvements, one exciting methodology involves the documentation and analysis of clinical workflows. Unfortunately, there is no industry standard tool which supports this, and many available workflow documentation technologies are not only proprietary, but technologically insufficient as well. Ideally, these workflows would be documented at a formal enough level to support their execution; this would allow the partial automation of documented clinical procedures. However, the difficulty involved in this automation effort is substantial: not only is there the irreducible complexity inherent to automation, but a number of the solutions presented so far layer on additional complication. To solve this, the author introduces Kinerja, a state-of-the-art execution environment for formally specified workflows. Operating on a subset of the academically and industrially proven workflow language YAWL, Kinerja allows for both human guided governance and computer guided verification of workflows, and allows for a seamless switching between modalities. Though the base of Kinerja is essentially an integrated framework allowing for considerable extensibility, a number of modules have already been developed to support the checking and executing of clinical workflows. One such module integrates symbolic execution which greatly optimizes the time and space necessary for a complete exploration of a workflow's state space.
Keywords: Model checking; Workflow; Formal verification; Kinerja; YAWL; Computer Science (0984)